2021
DOI: 10.5620/eaht.2021017
|View full text |Cite
|
Sign up to set email alerts
|

Detection of aflatoxin producing Aspergillus flavus from animal feed in Karnataka, India

Abstract: Aflatoxins are toxic carcinogenic secondary metabolite produced by Aspergillus flavus and are responsible for contamination in animal feed. The aim of the study was to determine the prevalence of aflatoxin contamination in animal feed in Karnataka state, India. The screening was performed by desiccated coconut agar and quantification of aflatoxin by liquid ammonia vapor test, TLC and ELISA. A total of 29 samples received from different places of Karnataka were analysed for aflatoxin B1. Out of 29 animal feed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
5
8
0
Order By: Relevance
“…The reverse side of the positive culture was turned plum red or reddish color when exposed to ammonia vapors. These results were similar to the study conducted in India where aflatoxigenic Aspergillus was detected in animal feed (Rajarajan et al, 2021). These results revealed that there was no correlation between this technique and the molecular (PCR) technique for the detection of aflatoxigenic Aspergillus.In the present study, the DNA was extracted from the fungal isolates from tobacco samples.…”
Section: Discussionsupporting
confidence: 87%
“…The reverse side of the positive culture was turned plum red or reddish color when exposed to ammonia vapors. These results were similar to the study conducted in India where aflatoxigenic Aspergillus was detected in animal feed (Rajarajan et al, 2021). These results revealed that there was no correlation between this technique and the molecular (PCR) technique for the detection of aflatoxigenic Aspergillus.In the present study, the DNA was extracted from the fungal isolates from tobacco samples.…”
Section: Discussionsupporting
confidence: 87%
“…A atoxin production by Aspergillus strains in vitro was assessed at the Crop Science Laboratory (MMUST) by the ammonia vapor test (Shekhar et al 2017;Rajarajan et al 2021). The Petri dishes containing the 8-day old Aspergillus cultures were turned upside-down to rest on the lids.…”
Section: Mycotoxin Production Estimates In Vitromentioning
confidence: 99%
“…Although Actellic® Super (C 11 H 20 N 3 O 3 PS + C 22 H 20 Cl 2 O 3 ) and Actellic® Gold (C 11 H 20 N 3 O 3 PS + C 8 H 10 C l2 N 5) promoted the growth of A. avus and Fusarium sp. in vivo, their capacity to promote the growth of these fungal strains could not be veri ed in vitro due to the presence of antagonistic microbial contaminants.A atoxin detection by ammonia vapour test in vitro indicated that A. avus strains grown on PDA-enriched with Super Blue Cross had the highest colour intensity, which is an indication of elevated production of a atoxins(Dufossé et al 2005;Rajarajan et al 2021). Enhanced production of a atoxins may be linked to nutritive components of the insecticide in the form of organic carbon, phosphorus and sulphur in Super Blue Cross (C 10 H 19 O 6 PS 2 ), which are consumed by the fungi for growth and mycotoxin production(Hamad et al 2023).…”
mentioning
confidence: 97%
“…Aflatoxins; They are secondary metabolites produced by some molds of Aspergillus, Penicillium and Rhizopus species, especially A. flavus and A. paraciticus. The clinical picture caused by aflatoxins in humans and animals is defined as "aflatoxicosis" (Rajarajan et al, 2021).…”
mentioning
confidence: 99%
“…Aflatoxins are compounds that have toxic effects on humans and all animal species. Besides carcinogenic, mutagenic, teratogenic, hepatotoxic and immunosuppressive properties of aflatoxins, it has been reported that they are effective in the formation of kidney damage and various organ tumors (Rajarajan et al, 2021).…”
mentioning
confidence: 99%